Transformation of the WHO Africa Region Secretariat: an exploratory study of the health policy lessons from health governance strengthening interventions for just and sustainable health systems - Bernard Hope Taderera (Frontiers in Public Health)
IntroductionThe World Health Organization African Region (WHOAFRO) Transformation Agenda initiated in 2015 has emerged as an important health leadership strengthening initiative in pursuing the 2030 health Sustainable Development Goals (SDGs) and universal health coverage. However, there remains need for research narrating health policy lessons from implementing it with a focus on Pro-Results Values, Smart Technical Focus, Responsive Strategic Operations, and Effective Communications and Partnerships, for just and sustainable public health systems in pursuing universal health coverage.AimThis study explored health policy lessons from the implementation of WHOAFRO Transformation from 2020 to 2023, and how this may help reinforce health systems governance on the continent.MethodsThis paper is generated from a wider study commissioned by WHOAFRO. The study design used was exploratory and qualitative. Secondary data were collected from publicly available purposively selected WHO documents. Narratives were first generated from the data, followed by coding and then thematic analysis.ResultsTraining and mentorship helped strengthen skills levels amongst health leaders which helped contribute efficiently toward Pro-Results Values. Interventions were directed to align with continental health system leadership goals for Smart Technical Focus. Leadership structures and systems were streamlined to strengthen organizational functions for the delivery of desired outcomes to achieve Responsive Strategic Operations. Collaboration with donors and health system governance partners at all levels helped broaden the resource base, which was complemented by the adoption of digital tools and hybrid work arrangements for Effective Partnerships and Communication.Discussion and conclusionTransforming health leadership in the Africa Region requires sustained effort to train health leaders to help strengthen health systems governance toward meeting the healthcare needs of the population. There is need for continued reinforcement of ethics values amongst health leadership to maintain a high moral standards for health workforce protection. There is also a need to sustain innovativeness in incorporating digital tools and hybrid work models into health governance for effective and efficient communication in health system leadership work. Strengthening partnerships between actors at all health governance levels helps contribute toward resource mobilization required for health system functioning for just and sustained pursuit of universal health coverage.